2002
DOI: 10.1029/2001jd001413
|View full text |Cite
|
Sign up to set email alerts
|

Twentieth century increase of atmospheric ammonia recorded in Mount Everest ice core

Abstract: ) concentrations suggests that a portion of the increase in NH 4 + concentrations could be contributed by enhanced atmospheric acidification. Anthropogenic ammonia emissions from enhanced agricultural activities and energy consumption over Asia in concert with population increase since the 1950s appear also to be a significant factor in the dramatic increase of NH 4 + concentrations during the last few decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 33 publications
3
60
0
Order By: Relevance
“…Modelling work is needed to separate out the influence of higher emissions from that of increased concentrations of sulfate and nitrate that may neutralize gaseous NH 3 , leading to greater NH 4 þ deposition. It is also suggested that a part of the increase may arise from the strengthening of natural ammonia emissions from plants and soils owing to increasing temperature [38]. Still, it seems likely that a large part of each increase is related to increased agricultural emissions, and that these ice-core trends can be used to constrain poorly known emission estimates for the regions influencing these core sites.…”
Section: Ice-core Records: Anthropogenic Change In Ammoniummentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling work is needed to separate out the influence of higher emissions from that of increased concentrations of sulfate and nitrate that may neutralize gaseous NH 3 , leading to greater NH 4 þ deposition. It is also suggested that a part of the increase may arise from the strengthening of natural ammonia emissions from plants and soils owing to increasing temperature [38]. Still, it seems likely that a large part of each increase is related to increased agricultural emissions, and that these ice-core trends can be used to constrain poorly known emission estimates for the regions influencing these core sites.…”
Section: Ice-core Records: Anthropogenic Change In Ammoniummentioning
confidence: 99%
“…factor 3 increase, 1960-1990) [19], East Rongbuk Glacier ( factor 2, 1950-1980) [38] and Belukha (factor 1.6, 1950-1980, followed by plateau) [33]. Modelling work is needed to separate out the influence of higher emissions from that of increased concentrations of sulfate and nitrate that may neutralize gaseous NH 3 , leading to greater NH 4 þ deposition.…”
Section: Ice-core Records: Anthropogenic Change In Ammoniummentioning
confidence: 99%
“…Regions of intensive agriculture are one of the principal sources of sustained ammonia flux into the atmosphere, arising both from fertilization operations and biogenic emission by crops and livestock. Intensive agriculture burgeoned markedly beginning around 1950 and has contributed to the dramatic increase in environmental ammonia observed since that time [Kang et al, 2002]. The area where the present work was carried out (the Imperial Valley in Southern California) is one such region of intensive agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…We measured a section of Core 2002 in the range 34.42 m to 35.27 m, where the summer and winter strata can be distinguished by seasonality of major ions Kang et al, 2002, and unpublished data; Fig. 2).…”
Section: Factors Controlling Gas Contentmentioning
confidence: 99%
“…The longest instrumental records from the region date back only to AD1935. Ice cores collected from high elevation glaciers in the Himalayas provided extended records of past climate in the region (Thompson et al, 2000;Kang et al, 2002;Qin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%